Inflammatory and deleterious role of gut microbiota-derived trimethylamine on colon cells - Jalandra, Rekha; Makharia, Govind K.; Sharma, Minakshi; Kumar, Anil (Frontiers in Immunology, 2023)
Trimethylamine (TMA) is produced by the intestinal microbiota as a by-product of metabolism of dietary precursors. TMA has been implicated in various chronic health conditions. However, the effect of TMA in the colon and the underlying mechanism was not clear. In this study, TMA exhibited toxic effects in vitro as well as in vivo. TMA-induced oxidative stress causes DNA damage, and compromised cell membrane integrity leading to the release of LDH outside the cells which ultimately leads to cell death. Besides, TMA also exhibited pronounced increase in cell cycle arrest at G2/M phase in both HCT116 and HT29 cell lines. TMA was found to be genotoxic and cytotoxic as the TMA concentration increased from 0.15 mM. A decreased ATP intracellular content was observed after 24 h, 48 h, and 72 h treatment in a time and dose-dependent manner. For in vivo research, TMA (100 mM, i.p. and intra-rectal) once a week for 12 weeks caused significant changes in cellular morphology of colon and rectum epithelium as assessed by H & E staining. TMA also significantly increased the infiltration of inflammatory cells in the colon and rectal epithelium indicating the severity of inflammation. In addition, TMA caused extensive mucosal damage and distortion in the epithelium, decrease in length of small intestine compared to control mice. In conclusion, these results highlight the detrimental effects of TMA in the colon and rectal epithelium.